Use of Plant Based Calcium Salt of Fatty Acids in Broiler Diets - Tabeidian, S.A.; Sadeghi, GH. (International Journal of Poultry Science, 2005)
This study carried out to evaluate the effect of plant based calcium salt of fatty acids (fat powder) on broiler chicken performance, carcass, organs and some plasma characteristics. A total of 320 one-day old broiler chicks of a commercial breed (Ross 308) from both sex with equal ratio were placed in 16 pens, twenty in each pen. Treatments were included Ca-salt of fatty acids at 0, 2.5, 5 and 7.5%. Each treatment replicated four times. Inclusion of fat powder had no significant effect on feed intake. Feeding different levels of fat powder significantly (P< 0.05) decreased weight gain in 7-21 and 7-49 day old chicks, and in other ages decreased weight gain numerically. Using of calcium salts of fatty acid significantly (P< 0.05) increased feed conversion ratio in 7-21 and 7-49 days old broiler chicken. Inclusions of fat powder in diet dose not affect carcass, abdominal fat, liver, pancreas, intestine and heart percentages. No significant differences were observed in plasma triglyceride, cholesterol, HDL and LDL. Our finding showed that using of fat powder could not improve broiler chickens performance.